The Changing Face of Padang: History of Urban Shape and Spatial Structure - Darmawan, Budi; Hakim, Lukmanul; Regita Cahyani Nazra, Endah; Puji Azizah, Faras; Praja Nata, Zaki; Irno (El Tarikh : Journal of History, Culture and Islamic Civilization, 2025)
This paper discusses the development of the spatial structure and layout of the city of Padang over time, from its early formation phase, through the colonial period, the era of independence, and into the post-independence period. The study employs a systematic historical approach through four main stages: heuristics (source collection), criticism (source evaluation and verification), interpretation (analysis of meaning and relationships between data), and historiography (narrative and analytical historical writing). The research findings indicate that the city of Padang has undergone significant changes in physical, social, economic, and functional aspects. The colonial period stands out as one of the most decisive phases, during which Padang rapidly developed as a center of government, trade, military, and transportation on the west coast of Sumatra. This development was driven by several strategic factors, including advantageous geographical location, well-organized colonial governance, the influx of migrants from various ethnic backgrounds, and the construction of urban infrastructure. Interactions between local residents and outsiders also enriched the city's cultural configuration and identity. Thus, this study provides a comprehensive and in-depth picture of how Padang has transformed over time as a result of a long, complex historical process influenced by various internal and external dynamics.